The Effectiveness of Task-Based Language Teaching Through Digital Projects in Reducing Foreign Language Speaking Anxiety among Students : Penelitian - Sayida Khoiratun Nisak (Jurnal Pustaka Cendekia Pendidikan, 2026)
Foreign Language Speaking Anxiety (FLSA) is an affective factor that may hinder students’ engagement in spoken English communication. Such anxiety may manifest as concerns about making mistakes, fear of negative evaluation, performance pressure, and difficulty participating in oral interaction. Recent scholarship indicates that speaking anxiety is a multidimensional phenomenon associated with psychological, linguistic, socio-affective, pedagogical, and technological factors (Khoirunnisa et al., 2026). In technology-mediated learning contexts, technology may function as a supportive resource for anxiety management, but under certain conditions it may also become a source of additional anxiety (Bárkányi & Brash, 2025; Huang & Liu, 2025). This study aimed to examine the effectiveness of Task-Based Language Teaching (TBLT) through digital projects in reducing FLSA among students at Institut Islam Al-Mujaddid Sabak. The study employed a quasi-experimental pretest-posttest control group design. The experimental group received instruction through a TBLT cycle integrated with digital projects, whereas the control group received conventional instruction. FLSA data were collected using an instrument adapted and validated through expert judgment, construct validation, and reliability testing. Data were analyzed using descriptive statistics, paired-samples t-tests, ANCOVA, and effect-size analysis. The results showed [insert actual research findings]. This study is expected to extend TBLT research by positioning the reduction of speaking anxiety as an affective learning outcome and by providing a contextualized instructional model for students in Islamic higher education.